IMPROVING THE ECONOMIC EFFICIENCY OF THE FISHERIES INDUSTRY OF THE REPUBLIC OF UZBEKISTAN THROUGH ECONOMETRIC MODELING - Madina Kuzibayevna Matyakupova; Aslbek Nurvaliyevich Tursunmurodov (International Journal of Literature and Language Studies, 2026)
Fish and fish products are among the essential dietary foods that are highly beneficial for the human body and occupy an important place in the human diet. It is well known that fish meat differs from the meat of other animals in that it is easily and rapidly digested by the human body. Fish meat is rich in vitamin D, which helps maintain the normal metabolism of calcium and phosphorus in the human body. It also prevents rickets in young children and even in animals kept indoors during the late autumn and winter months, and plays a significant role in the treatment of patients suffering from this disease. In addition, fish unsuitable for human consumption, as well as fish obtained from the waste products of fish-processing enterprises, serve as valuable additives that enrich the feed ration of agricultural animals and poultry with various proteins and vitamins.